Handbook of Population - Poston Jr., Dudley L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
"Demography is a dynamic field that is constantly evolving, which is why the 2006 edition of The Handbook of Population was such a welcome update to earlier summation prepared in 1959 by Philip Hauser and Dudley Duncan. The second edition of The Handbook is likewise a welcome addition to the literature given the rapid pace of change in demographic research today. Not only have earlier updates on new topics such as biodemography and political demography been expanded, the new edition also contains entirely new chapters on emerging issues of demographic interest such as obesity, inequality, and adoption. Editor Dudley Poston continues to provide a great service to the field by keeping demographers abreast of the latest developments in population science." (Douglas S. Massey, Princeton, USA) "The 2nd edition of the Handbook of Population covers the major topics of the discipline of demography, including current substantive, methodological and theoretical issues of interest, as well as new and emerging topics in the field. In addition to revised, updated and extended chapters that were included in the 1st edition, this 2nd edition of the Handbook brings to the forefront entirely new chapters covering such major themes as children, adoption, sexuality, inequality, population psychology, rural demography, and obesity. Chapters in this Handbook will expand our knowledge of the field, and will raise awareness of the causes and the consequences of demographic behavior and events in societies throughout the world. This 2nd edition will also serve as a reference in the field of population studies for years to come. It will generate new questions and research ideas and will positively impact the growth, development, and expansion of demography.".
Prologue; Dudley L. Poston, Jr., and Michael Micklin -- Part I. Population Structure -- Chapter 1. Age and Sex; Dudley L. Poston, Jr -- Chapter 2. Population Distribution and Suburbanization; Avery M. Guest and Susan K. Brown -- Chapter 3. Family Demography; Lynne Casper -- Chapter 4. Demography of Gender; Nancy E. Riley -- Chapter 5. Demography of Aging; Marc Garcia and Kyriakos Markides -- Chapter 6. Demography of Race and Ethnicity; Rogelio Saenz and M. Cristina Morales -- Chapter 7. Demography of Children; William P. O'Hare -- Chapter 8. Demography of Adoption; Mary Ann Davis -- Chapter 9. Demography of the Labor Force; Joachim Singelmann and Teresa A. Sullivan -- Chapter 10. Demography of Sexuality; Amanda K. Baumle -- Chapter 11. Demography of Poverty; Joachim Singelmann -- Chapter 12. Demography of Inequality; Mark Mather and Beth Jarosz -- Part II. Population Processes -- Chapter 13. Fertility; S. Philip Morgan -- Chapter 14. Infant Mortality; Bethany DeSalvo and Maria Perez Patron -- Chapter 15. Adult Mortality; Richard G. Rogers, Robert A. Hummer and Patrick M. Krueger -- Chapter 16. Internal Migration; Michael J. White and David P. Lindstrom -- Chapter 17. International Migration; Susan K. Brown and Frank D. Bean -- Chapter 18. Demography of Social Stratification; Arthur Sakamoto and Daniel A. Powers -- Part III. Population and the Social Sciences -- Chapter 19. Social Demography; David L. Brown -- Chapter 20. Population Psychology; Toni Falbo and Joseph L. Rodgers -- Chapter 21. Organizational and Corporate Demography; Glenn R. Carroll and Olga M. Khessina -- Chapter 22. Urban Demography; Mark A. Fossett -- Chapter 23. Rural Demography; Katherine J. Curtis and László J. Kulcsár -- Chapter 24. Anthropological Demography; David I. Kertzer -- Chapter 25. Economic Demography; Andrew Mason -- Chapter 26. Historical Demography; Myron Gutmann and Emily Merchant -- Chapter 27. Ecological Demography; Dudley L. Poston, Jr -- Chapter 28. Biodemography; James R. Carey and James W. Vaupel -- Chapter 29. Mathematical Demography; Kenneth C. Land, Claire Yang and Yi Zeng -- Chapter 30. Political Demography; Michael S. Teitelbaum -- Part IV. Applied Demography -- Chapter 31. Fertility Planning; John Cleland and Joseph E. Potter -- Chapter 32. Small Area and Business Demography; Peter A. Morriso and Stanley K. Smith -- Chapter 33. The Demography of Population Health; David F. Warner and Mark D. Hayward -- Chapter 34. Population Policy; John F. May -- Epilogue: Needed Research in Demography; Dudley L. Poston, Jr. and Amanda K. Baumle. .
Keywords: Demography; Population; Social policy; Social structure; Equality; Population and Demography; Social Policy; Social Structure